Evaluation of Der p 10 in a Cohort of European Children: Role of Molecular Diagnostics and Clinical Features - Cristiana Indolfi; Giulio Dinardo; Angela Klain; Alessandra Salvatori; Marica Esposito; Viviana Vela; Fabio Decimo; Giorgio Ciprandi; Michele Miraglia del Giudice (Journal of Immunology Research)
Background. Allergy toward the dust mite is steadily increasing on the European continent. This sensitization may be a risk factor for developing sensitization to other mite molecules such as tropomyosin Der p 10. This molecule often correlates with food allergy and the risk of anaphylaxis after ingesting mollusks and shrimps. Materials and Methods. We analyzed the sensitization profiles by ImmunoCAP ISAC of pediatric patients from 2017 to 2021. The patients under investigation were being followed for atopic disorders such as allergic asthma and food allergies. The study aimed to analyze the prevalence of sensitization toward Der p 10 in our pediatric population and assess the related clinical symptoms and reactions after ingestion of foods containing tropomyosins. Results. This study included 253 patients; 53% were sensitized toward Der p 1 and Der p 2; 10.4% were also sensitized to Der p 10. Assessing patients sensitized to Der p 1 or Der p 2, and Der p 10, we observed that 78.6% were affected by asthma (p<0.005) and had a history of prior anaphylaxis after ingestion of shrimp or shellfish (p<0.0001). Conclusion. The component-resolved diagnosis gave us a deeper understanding of patients’ molecular sensitization profiles. Our study showed that a fair proportion of children sensitive to Der p 1 or Der p 2 are also sensitive to Der p 10. However, many patients sensitized to all three molecules had a high risk of asthma and anaphylaxis. Therefore, the assessment of Der p 10 sensitization should be considered in atopic patients with sensitization to Der p 1 and Der p 2 to avoid encountering possible adverse reactions after ingesting foods containing tropomyosins.